Kajian Etnobotani Tanaman Jengkol (Pithecellobium jiringa) di Desa Cimanggu Kecamatan Cibeber Kabupaten Cianjur - Tri Cahyanto; Muhammad Efendi; Deasy Rahmawati; Yuni Kulsum; Balqis Tri Oktaria; Iman Aulia Rahman; Afriansyah Fadillah; Jalaludin (Journal of Tropical Ethnobiology, 2021)
Indonesia has various tribes or ethnicities scattered in various islands. These tribes have a wealth of knowledge, and local wisdom as a hereditary tradition that are useful for the modern society because of their closeness to nature, for example the tradition of managing plants traditionally. Jengkol (Pithecellobium jiringa (Jack) Prain.) is widely known by the Indonesian community, easily found in forests so that a few people cultivate the plant. Cimanggu Village is an area where people still have knowledge from generation to generation in terms of managing jengkol. This study aimed to document the ethnobotany of jengkol as a food plant. The study employed a qualitative descriptive method using interview with 30 respondents obtained by snowball sampling technique. The results showed that only 10% of respondents still remembered the processing of Jengkol. The abundance of Jengkol in Cimanggu Village has decreased due to a low interest in the cultivation of Jengkol. There are three types of jengkol, i.e. Jengkol Ngora, Jengkol Kolot, and Sepi, that are known within the community, each Jengkol has different characteristics, processing methods, and uses.